Early Pliocene foraminifera-bound nitrogen isotopes and oxygen isotopic composition of seawater from ODP Sites 999 and 1241 - Jesse R Farmer; Alfredo Martínez-García; Lori Sentman; Ralf Schiebel; Anthea Arns; Maayan Yehudai; Ralf Tiedemann; Daniel M Sigman; Gerald H Haug (PANGAEA, 2025)
We investigated the Early Pliocene (5.3 to 3.6 million years ago) history of oceanic exchange across the Central American Seaway using a suite of geochemical measurements on planktonic foraminifera at Ocean Drilling Program Sites 165-999A (Caribbean Sea) and 1241 (Eastern Tropical North Pacific). Foraminifera-bound nitrogen isotopes were performed on Trilobatus sacculifer and combined samples of Globortalia menardii and Globortalia tumida, and measured via the persulfate-denitrifier methodology at Max Planck Institute for Chemistry. We also collated existing planktonic foraminifer oxygen isotope measurements and Mg/Ca in T. sacculifer from Sites 165-999A and 202-1241 (Haug et al., 2001; Groeneveld & Tiedemann, 2005; Steph et al., 2006). These data were used to calculate sea surface temperature and the oxygen isotope composition of seawater using PSU Solver (Thirumalai et al., 2016).